Cerebral sinovenous thrombosis associated with head/neck infection in children: Clues for improved management. (29th June 2022) - Narcy, Lucie; Durand, Sabine; Grimaud, Marion; Leboucq, Nicolas; Grevent, David; Cambonie, Gilles; Couloigner, Vincent; Rivier, François; Meyer, Pierre; Kossorotoff, Manoelle
Abstract: Aim: To compare paediatric patients with cerebral sinovenous thrombosis (CSVT) with and without head/neck infection to improve management of the condition. Method: We conducted a bicentric retrospective study of consecutive children (neonates excluded) with radiologically confirmed CSVT, comparing children with a concurrent head/neck infection and children with other causes. Results: A total of 84 consecutive patients (46 males and 38 females) with a median age of 4 years 6 months (range 3 months–17 years 5 months) were included. Associated head/neck infection was identified in 65.4% of cases and represented the main identified CSVT aetiology. Children in the head/neck infection group displayed a milder clinical presentation and less extensive CSVT. Median time to complete recanalization was significantly shorter in this group (89 days [interquartile range 35–101] vs 112.5 days [interquartile range 83–177], p = 0.005). These findings were even more pronounced in the subgroup of patients with otogenic infection and no neurological sign. Interpretation: As CSVT in the setting of an otogenic infection and no neurological sign seems to represent a milder condition with a shorter course, these results suggest adapting current recommendations: consider earlier control imaging in paediatric otogenic CSVT, and shorter anticoagulant treatment if recanalization is obtained. What this paper adds: Children with cerebral sinovenous thrombosis related to head/neck infections have a milder clinical presentation. They also have a shorter recanalization time, especially if there is otogenic infection without neurological symptoms. What this paper adds: Children with cerebral sinovenous thrombosis related to head/neck infections have a milder clinical presentation. They also have a shorter recanalization time, especially if there is otogenic infection without neurological symptoms.